Education Policy in Turkey During the Reign of Recep Tayyib Erdogan - Zari’a Istiqomah; Luqman MoHa (Journal of Social Science Utilizing Technology, 2023)
Background. Islamic education is an effort to develop a person's faith and charity in order to have attitudes and behaviour that are in line with Islamic teachings, and to realise the welfare of life. This approach is based on Islamic laws that aim to form the main Muslim personality in accordance with Islamic teachings. Turkey is one of the Muslim nations that has an urgent role in the development of Islamic culture. Purpose. This article aims to be an initial assumption to raise awareness of the importance of education policy changes during the reign of Recep Tayyib Erdogan. Method. This research uses a qualitative method with a descriptive approach based on the writings of education experts. The focus of this article is on education policies that have been implemented by considering dynamic actual conditions. Analysis of the writings of education experts, both through reading books and related journals, is used as a reference to describe education policy. Results. The results of this study are Some important aspects of education policy in Turkey during Erdogan's reign include: transformation of the education system, Improvement of Islamic religious education, Introduction of Islamic curriculum, Character development, Improvement of teacher quality, Expansion of preschool education, Parental involvement and emphasis on technology education.   Recep Tayyib Erdogan's Education Policy in Turkey has implemented several significant education policies since he took over the government in 2003. Conclusion. Erdogan's education policy in Turkey includes system transformation, improvement of Islamic religious education, Islamic curriculum, character development, improvement of teacher quality, expansion of preschool education, parental involvement, and emphasis on technology education since 2003.